2021
DOI: 10.1016/j.quaint.2020.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic imprints of landscape evolution in the Bhilangana and Mandakini basin, Garhwal Himalaya, India: A geospatial approach

Abstract: Torrential rains, landslides, and seismic activity are the common factors that are causing unprecedented damage to life, property and infrastructure in Mandakini and Bhilangana basins of Garhwal Himalaya. Owing to such conditions, we demonstrate the feedback this landscape in Garhwal Himalaya in response to episodic tectonic uplift and monsoon precipitation. We calculated conventional geomorphic parameters to access the tectonic deformation across the major thrusts and faults. We further analyzed the normalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(5 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Validity of such a model would require a deeper insight and thus remains as a possibility to explain arc-parallel shear within NW Indian Himalaya. Taloor et al (2020) identified five levels of river terraces and based on geomorphic studies from the Garhwal LHS. Pandey et al (2005) recorded five stages of uplift.…”
Section: Most Suitable Model(s) For Arc-parallel Extension In Nw Indi...mentioning
confidence: 99%
“…Validity of such a model would require a deeper insight and thus remains as a possibility to explain arc-parallel shear within NW Indian Himalaya. Taloor et al (2020) identified five levels of river terraces and based on geomorphic studies from the Garhwal LHS. Pandey et al (2005) recorded five stages of uplift.…”
Section: Most Suitable Model(s) For Arc-parallel Extension In Nw Indi...mentioning
confidence: 99%
“…Validity of such a model would require a deeper insight and thus remains as a possibility to explain arc-parallel shear within NW Indian Himalaya. Taloor et al (2020) identified five levels of river terraces and based on geomorphic studies from the Garhwal LHS. Pandey et al (2005) recorded five stages of uplift.…”
Section: Most Suitable Model(s) For Arc-parallel Extension In Nw Indian Lhsmentioning
confidence: 99%
“…Differential upliftment, tilting in the Bhimtal Naukuchiatal basin all along and across the Nagrigaon Naukuchiatal fault, sattal fault and salari thrust is observed which is shown in the Figure2and the degree of tilting which is represented by AF values. Similarly we estimated channel sinuosity for all the tributary streams of main channel and observed that the sinuosity of trunk and tributary streams are varies from 1.06 to 1 29. which indicate most of the streams are braided in nature.…”
mentioning
confidence: 91%
“…22,23,24,25,26 Since neotectonic activity can have a substantial impact on fluvial systems, qualitative and quantitative investigations of drainage pattern are valuable for evaluating how it affects geomorphic processes and landscape evolution 22,27 Some of the notable characteristics of the tectonically formed landforms in vicinity of thrusts/faults zones of the Himalaya in general and Uttarakhand Himalaya in particular are the active and settled landslides, formation of palaeolakes, raised paired or separated terraces, incision, entrenched meandering, change of valley channels, occurrence of deep valley, waterfalls and displacement of previous faults by the later ones . 28,29,30,31,32,33,34,35,36,37 In tectonically active regions, morphometric tools are widely used to understand how tectonics affects the landscape. 38,39,40,41,42,43,44,45 A number of studies have shown that the mountainfront in the area is affected by neotectonic.…”
Section: Introductionmentioning
confidence: 99%